DIVERSITY, DISTRIBUTION, AND UTILIZATION OF ORCHIDS SPECIES (Orchidaceae) IN BODOGOL FOREST, GEDE PANGRANGO NATIONAL PARK, WEST JAVA - Asep Sadili; Siti Sundari (Widyariset, 2017)
To investigate the diversity, distribution, and utilization of orchid, a study was conducted in Bodogol forest of Gede Pangrango National Park (TNGP). Around 82 species of 41 genera of orchids were identified in this area which consisted of 58 species of epiphytes orchids and 24 species of terrestrial orchids. The genera of Agrostophyllum, Dendrobium, and Eria were the most commonly found orchid in this area. Distribution of orchid species varied from India to Pacific islands, including Japan. Among recognized six endemic orchid species of Java island, two new records of orchids at GPNP were determined, i.e. Neuwiedia veratifolia and N. zollingeri var. javanica. In general, the orchids in Bodogol forest have not been economic commodities priority yet, but several species were potential to be developed for utilization.